Assessing the level of environmental information disclosure by listed companies on the stock market in Vietnam - Thi Kim Tuyen Nguyen; Ngoc Tien Nguyen; Thi Mai Huong Nguyen (My University, 2019)
Assessing the level of environmental information disclosure by listed companies on the stock market in Vietnam
Keywords: Environmental disclosure; Listed companies; Vietnam